Echinacea-induced cytosolic Ca2+ elevation in HEK293 - Nikolau Basil J; Rizshsky Ludmila; Jeftinija Srdija; Jeftinija Ksenija; Rowe Eric W; Wu Lankun; McKay Jodi; Kohut Marian; Wurtele Eve (BMC Complementary and Alternative Medicine, 2010)
Abstract Background With a traditional medical use for treatment of various ailments, herbal preparations of Echinacea are now popularly used to improve immune responses. One likely mode of action is that alkamides from Echinacea bind to cannabinoid type 2 (CB2) receptors and induce a transient increase in intracellular Ca2+. Here, we show that unidentified compounds from Echinacea purpurea induce cytosolic Ca2+ elevation in non-immune-related cells, which lack CB2 receptors and that the Ca2+ elevation is not influenced by alkamides. Methods A non-immune human cell line, HEK293, was chosen to evaluate E. purpurea root extracts and constituents as potential regulators of intracellular Ca2+ levels. Changes in cytosolic Ca2+ levels were monitored and visualized by intracellular calcium imaging. U73122, a phospholipase C inhibitor, and 2-aminoethoxydiphenyl borate (2-APB), an antagonist of inositol-1,4,5-trisphosphate (IP3) receptor, were tested to determine the mechanism of this Ca2+ signaling pathway. E. purpurea root ethanol extracts were fractionated by preparative HPLC, screened for bioactivity on HEK293 cells and by GC-MS for potential constituent(s) responsible for this bioactivity. Results A rapid transient increase in cytosolic Ca2+ levels occurs when E. purpurea extracts are applied to HEK293 cells. These stimulatory effects are phospholipase C and IP3 receptor dependent. Echinacea-evoked responses could not be blocked by SR 144528, a specific CB2 receptor antagonist, indicating that CB2 is not involved. Ca2+ elevation is sustained after the Echinacea-induced Ca2+ release from intracellular Ca2+ stores; this longer-term effect is abolished by 2-APB, indicating a possible store operated calcium entry involvement. Of 28 HPLC fractions from E. purpurea root extracts, six induce cytosolic Ca2+ increase. Interestingly, GC-MS analysis of these fractions, as well as treatment of HEK293 cells with known individual and combined chemicals, indicates the components thought to be responsible for the major immunomodulatory bioactivity of Echinacea do not explain the observed Ca2+ response. Rather, lipophilic constituents of unknown structures are associated with this bioactivity. Conclusions Our data indicate that as yet unidentified constituents from Echinacea stimulate an IP3 receptor and phospholipase C mediation of cytosolic Ca2+ levels in non-immune mammalian cells. This pathway is distinct from that induced in immune associated cells via the CB2 receptor.